Risk Acceptance and Expectations of Laryngeal Allotransplantation - Jo, Hyun Kyo; Park, Jang Wan; Hwang, Jae Ha; Kim, Kwang Seog; Lee, Sam Yong; Shin, Jun Ho (Archives of Plastic Surgery, 2014)
Background Laryngeal allotransplantation (LA) is a technique involving transplantation of a deceased donor's larynx into a recipient, and it may be substituted for conventional laryngeal reconstruction. There are widely different views on LA, as the recipient is administered continuous, potentially life-threatening, immunosuppressive therapy for a functional or aesthetic result, which is not directly related to life extension. The purpose of this study was to analyze the difference in risk acceptance and expectations of LA between four population groups.Methods A survey was performed to examine patients' risk acceptance and expectations of LA. The survey included 287 subjects in total (general public, n=100; kidney transplant recipients, n=53; post-laryngectomy patients, n=34; doctors, n=100), using a Korean translated version of the louisville instrument for transplantation (LIFT) questionnaire.Results All four groups responded differently at various levels of their perception in risk acceptance and expectations. The kidney transplant recipients reported the highest risk acceptance and expectations, and the doctor group the lowest.Conclusions This study examined the disparate perception between specific population groups of the risks and benefits of using LA for the promotion of the quality of life. By addressing the information gaps about LA in the different populations that have been highlighted from this survey, we suggest that LA can become a more viable alternative to classical surgery with resultant improved quality of life for patients.
Keywords: Larynx; Reconstructive surgical procedures; Patient acceptance of healthcare; Data collection